Length-weight relationships of marine species caught by five gears from the Black Sea - KASAPOGLU, N.; DUZGUNES, E. (Mediterranean Marine Science, 2013)
Length-weight (L-W) relationships were presented from 10475 individuals for 19 fish, 4 mollusks, 2 crustacean species during January 2009-November 2011. The mean value of ‘parameter b’ was estimated 2.881±0.399 ranged from 1.758 to 3.616 were isometric (i.e. Scorpeana porcus, Pomatous saltatrix and Neogobius melanostomus). L-W relationships for all studied species were significantly linear (0.819<R2<0.987).